KEBIJAKAN LUAR NEGERI PEMERINTAHAN AMERIKA SERIKAT TERHADAP PROGRAM NUKLIR KOREA UTARA - Pah Levi; Mohammad Riezky (Jurnal Akrab Juara, 2019)
The United States Foreign Policy towards the North Korean Nuclear Program to control, supervise and stop North Korea from producing nuclear. This is related to the position of the United States as the controller of international security and there is a national interest in the United States Government. This study aims to explain / describe the United States foreign policy towards the North Korean Nuclear Program. The data used are secondary data because international relations scientific research uses qualitative data. The data collection method used in this study is the literature of books, websites. Techniques of data analysis using qualitative analysis. The results of the study indicate that the United States Foreign Policy to reduce the North Korean Nuclear Program with Strategic Patience and the Detterence Concept.